2008
DOI: 10.1111/j.1748-5827.2008.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease in research beagle dogs – an epidemiological study

Abstract: Periodontal disease in terms of clinical attachment loss greater than equal to 1 mm and pocket depth greater than equal to 4 mm is common in beagle dogs, but the major disease burden is carried by only a few dogs. The prevalence increases with increased age but is high already at the age of two years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
111
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(124 citation statements)
references
References 20 publications
(56 reference statements)
7
111
2
4
Order By: Relevance
“…5), but this correlation was not signifi cant, probably because of the small number of dogs used in the present study. Our results are in agreement with previous results that periodontal disease is the most widespread oral disease in dogs and incidence increases with advancing age (Kortegaard et al, 2008;Hirai et al, 2013). Further work is also required to confi rm this hypothesis.…”
Section: Correlations Between Vsc Levels and Agesupporting
confidence: 83%
“…5), but this correlation was not signifi cant, probably because of the small number of dogs used in the present study. Our results are in agreement with previous results that periodontal disease is the most widespread oral disease in dogs and incidence increases with advancing age (Kortegaard et al, 2008;Hirai et al, 2013). Further work is also required to confi rm this hypothesis.…”
Section: Correlations Between Vsc Levels and Agesupporting
confidence: 83%
“…Periodontal disease is the most widespread oral disease in dogs and prevalence estimates of between 44% and 64% have been reported (Butkovi c et al, 2001;Kyllar and Witter, 2005;Kortegaard et al, 2008;Hamp et al, 1984). It is generally accepted that the build-up of plaque bacteria on the tooth surface causes periodontal disease, however the specific organisms involved in the initiation of disease and subsequent events are not yet known (Van Dyke, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…In a previous study of Beagle dogs [15] we have shown that the prevalence of both clinical attachment loss (CAL) ≥1 mm and pocket probing depth (PPD) ≥4 mm are relatively high even in younger dogs, but also that only a minority of the dogs have such clinical signs of PD in more than a few teeth. Hence, a minority of dogs carry the major PD burden.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies suggest that PD among dogs [15-18], in corroboration with PD in humans [19-21], follows a particular pattern within the dentition, which may be utilized to develop a tool for screening dogs for PD. A total periodontal disease index for disease estimation has been described; however this index aims at estimating disease extent within a dentition, not as in this present study disease occurrence within a population [22,23].…”
Section: Introductionmentioning
confidence: 99%